A little of Nepal: Nepali diaspora in the US in an age of globalization - Nath, Lopita (Bodhi: An Interdisciplinary Journal, 2010)
This article, while examining the Nepalis' efforts to negotiate between two worlds (hostland and homeland) through the striking realities of belonging to both, also examines issues of identity, assimilation, adjustment and notions of home expressed in their struggles to create a new sense of themselves in the process of self-construction which immigrants commonly encounter in the USA. The study is exploratory in nature and is expected to fill an important gap in scholarship of the South Asian as well as the Nepali diaspora in the United States. DOI: 10.3126/bodhi.v3i1.2817 Bodhi Vol.3(1) 2009 p.106-119